The ComPact UniLock 2.0/2.4 system and its clinical application in small animal orthopedics - Keller, M. A.; Voss, K.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
This study describes the titanium ComPact UniLock 2.0/2.4™ locking plate system (Stratec Medical, Oberdorf, Switzerland) and reports its application in nine selected clinical cases. The system was found useful for a variety of indications. Three categories of clinical applications are illustrated. They include (a) long bone fractures, (b) cervical spinal fractures and instabilities and (c) joint instabilities and luxations. A brief introduction to the system has already been published (1).
Keywords: UniLock; internal fixator; biological internal fixation